Correlation of microstructural and mechanical properties of geopolymers produced from fly ash and slag at room temperature. (10th December 2018) - Yazdi, Mohammad Ali; Liebscher, Marco; Hempel, Simone; Yang, Jian; Mechtcherine, Viktor
Highlights: High strength geopolymers were developed for curing at room temperature. Substitution of fly ash with GGBS by more than 50% leads to increase in flexural strength only. The freeze-drying is a desirable method for pre-conditioning of geopolymers for microstructural analysis. Good correlation is observed between the microstructure and strength development of geopolymers. Abstract: High strength fly ash (FA)-based geopolymer pastes containing slag were characterized by means of X-ray diffraction (XRD), thermogravimetry (TGA), and environmental scanning electron microscopy (ESEM). Various ratios of FA were replaced with ground granulated blast furnace slag (GGBS) to enhance the early strength development of the geopolymers cured at room temperature. Compressive and flexural strength tests were conducted to determine the mechanical properties, and mercury intrusion porosimetry (MIP) measurements were carried out to investigate the microstructure of the hardened geopolymers. A new pre-conditioning drying method for MIP investigations was applied and its effects on the GPs' microstructure were evaluated. The comparison of results showed that freeze-drying by using liquid nitrogen could be a great alternative to the conventional drying methods for geopolymers. The compressive and flexural strengths of geopolymers containing slag reached up to around 100 MPa and 10 MPa, respectively. The decreasing porosity of the geopolymers correlated well with the obtained increasing values of the compressive strength. However, neither of them noticeably improved when over 50% of FA was replaced by GGBS, while a further increase in the flexural strength was observed.